56 The medsafer pilot results: electronic deprescribing for hospitalized older adults with polypharmacy. (20th August 2018) - McDonald, Emily; Lee, Todd; Wu, Peter; Downar, James; Goodine, Carole
Abstract : Polypharmacy is a staggering problem and overmedicated seniors are an unseen epidemic; naearly two thirds of community dwelling older adults are prescribed 5 or more medications. Polypharmacy is associated with harm from adverse drug events including hospitalization, and even death. Deprescribing is an intervention that rationally reduces and eliminates harmful drugs. However, the process can be time consuming and resource intensive. MedSafer is a not-for-profit Canadian electronic tool that automates deprescribing and generates individualized, prioritized deprescribing opportunities for older adults. It has been successfully piloted on more than 3000 hospitalized patients and has been shown to be fast, safe, and effective. The MedSafer pilot study took place on four clinical teaching units at three Canadian hospital Centres in Ontario and Québec. The pilot included 924 hospitalized eligible patients age >65 who took 5 or more medications. At admission to the hospital, there were 779 patients (84%) who were taking 1 or more potentially inappropriate medications (PIM) identified by MedSafer, and who were included in the primary outcome. Similar to the control population, the median age of patients who had a deprescribing opportunities report provided to their usual treating medical team was 81 (IQR 74–88) and 53% were female. Patients were highly co-morbid and close to 10% had a history of dementia, delirium, or recurrent falls. More than 25% were moderately to severely frail. Baseline rates of deprescribing at study sites was high. Of 382 control patients, 179 (46.9%) had one or more PIMs stopped. In the intervention, 217 of 397 (54.7%) had one or more PIMs stopped. Odds ratio for discontinuation during the six-week intervention phase (after adjustment for hospital level clustering) was 1.24 (95% CI 1.02 to 1.50). This implied an absolute increase of 7.8% of patients having 1 or more PIMs stopped (Number needed to treat or NNT=13). MedSafer is an innovation that automates the time-consuming task of cross-referencing complex medical conditions with oftentimes upwards of 10–15 medications, provides tapering instructions when idicated, and pairs with patient directed educational brochures for deprescribing. MedSafer is extremely well suited to be highly scalable and spread across jurisdictions and facilities. The tool is fully bilingual making it usable across all provinces in Canada. A further 2000 patients have been enrolled in an ongoing trial and an Application Programming Interface (API) is set to automate deprescribing opportunities for all patients in long term care facilities in the province of New Brunswick in Summer 2018. Objectives: Present the results of the largest Canadian deprescribing trial taking place in acute care hospitals. What does polypharmacy and depscribing look like on the clinical teaching units of several large Canadian hospital centers? Learn what the barriers are to automating the deprescribing process across jursidictions (community–dwelling, long–term care, acute and chronic hospitalization). Describe how technology can overcome the time–consuming and complex process of deprescribing in an era of mega–polypharmacy. What is an application programming interface and how can it help us manage polypharmacy? Discuss MedSafer as an framework for a national academic collaboration that successfully addresses polypharmacy by uniting healthcare providers and researchers with a clinical background in Geriatric Medicine, Internal Medicine, and Geriatric Pharmacotherapy. Method: The pilot study methodology is a before and after feasibility study that took place on four clinical teaching units in Quebec and Ontario with control for hospital level clustering. A second ongoing study is a stepped wedge cluster randomized controlled trial with three clusters and 11 hosptals across Quebec, Ontario, and Central/western Canada, that is powered for a reduction in adverse drug events at 30 days post hospital discharge (6000 patients; enrolment 30% complete).The results of the 1000 patient MedSafer trial will be presented either as an oral presentation or in workshop format. We will expore the path we took in developing the software and then deploying the intervention. We will discuss successes and barriers to implementing a large scale deprescribing intervention, that to date, has enrolled close to 3000 patients across the country in two official languages. Results: Pilot study: of 924 hospitalized eligible patients age>65 who took 5 or more medications, 779 (84%) had 1 or more PIMs identified at admission and were included in the primary outcome. Similar to the control population, the median age of patients was 81 (IQR 74–88) and 53% were female. Patients were highly co-morbid and more than 25% were moderate to severely frail. Baseline rates of deprescribing in the pilot study sites was high. Of 382 control patients, 179 (46.9%) had one or more PIMs stopped. In the intervention, 217 of 397 (54.7%) had one or more PIMs stopped. Odds ratio for discontinuation during the six-week intervention phase (after adjustment for hospital level clustering) was 1.24 (95% CI 1.02 to 1.50). This implied an absolute increase of 7.8% of patients having 1 or more PIMs stopped (Number needed to treat=13). Conclusions: MedSafer is an innovation that automates the time-consuming task of cross-referencing complex medical conditions with oftentimes upwards of 10–15 medications, provides tapering instructions when indicated, and pairs with patient directed educational brochures for deprescribing. MedSafer is extremely well suited to be highly scalable and spread across jurisdictions and facilities. The tool is fully bilingual making it usable across all provinces in Canada. We will present what is involved in the designing of an application programming interface (API) and how this technology can allow for the processing of thousands of patient records, in order to provide clinicians with concise, real-time, patient deprescribing opportunities. Future directions for the MedSafer API is the automation of deprescribing opportunities for all patients in long term care facilities in the province of New Brunswick, beginning in the Summer of 2018.